Informal science, technology, engineering and math learning conditions to increase parent involvement with young children experiencing poverty - Zucker, Tricia A.; Maldonado, Gloria Yeomans; Assel, Michael; McCallum, Cheryl; Elias, Cindy; Swint, John M.; Lal, Lincy (Frontiers in Psychology, 2022)
Broadening participation in early science, technology, engineering and math (STEM) learning outside of school is important for families experiencing poverty. We evaluated variations of the Teaching Together STEM pre-kindergarten program for increasing parent involvement in STEM learning. This informal STEM, family engagement program was offered in 20 schools where 92% of students received free/reduced lunch. The core treatment included a series of family education workshops, text messages, and family museum passes. The workshops were delivered at school sites by museum outreach educators. We randomly assigned schools to business-as-usual control or one of three additive treatment groups. Using an additive treatment design, we provided the core program in Treatment A, we added take-home STEM materials in Treatment B, and added materials + parent monetary rewards in Treatment C. The primary outcome was parent involvement in STEM (n = 123). There were no significant impacts of any treatment on parent involvement; however, the groups that added take-home materials had larger effect sizes on parent involvement at posttest (ES = −0.08 to 0.18) and later, kindergarten follow-up (ES = −0.01 to 0.34). Adding parent monetary rewards only produced short-term improvements in parent involvement that faded at follow-up. We discuss implications for other community-sponsored family engagement programs focused on informal STEM learning, including considering characteristics of families who were more versus less likely to attend. These null findings suggest that alternatives to in-person family education workshops should be considered when parents are experiencing poverty and have competing demands on their time.